Perfilhamento e produção de forragem do capim faixa-branca submetido a frequências de desfolhação - Rizato, Cesar Augusto (2017)
This study was conducted to evaluate the tillering dynamics, forage production, and use potential of digitgrass subjected to four defoliation intensities: Very High (25 cm), High (35 cm), Medium (45 cm), and Low (55 cm), evaluated in two periods of the year (higher and lower insolation) from January 2015 to January 2016. A randomized-block design with four replicates was adopted and measures repeated over time. Increasing defoliation frequencies increased the number of tiller generations, tiller appearance and mortality rates, aerial tiller density, and forage use potential and reduced tiller survival rate, daily stem production, daily leaf senescence, total daily production, and net daily accumulation of forage. Daily leaf production was lower at the Very High frequency as compared with the other frequencies. In the period of lower insolation, daily leaf senescence and tiller appearance and mortality rates were higher, while survival rate, balance, aerial tiller density, daily stem production, net daily accumulation of forage, and forage use potential were lower. Basal tiller density increased as the defoliation densities were elevated, with higher values observed during the period of greater insolation at the Very High and High frequencies. The Very High defoliation frequency did not provide good plant development, whereas the Low frequency led to increased stem production. The defoliation frequencies and times of the year evaluated here do not change the population stability of digitgrass plants when irrigated, thus ensuring its persistence. Higher defoliation frequencies result in greater tiller renewal in digitgrass. The High and Medium defoliation frequencies are more suitable for the defoliation of digitgrass, promoting a larger proportion of leaves in relation to stems.